Analisis Rekomendasi untuk Meningkatkan Nilai Capability Level Domain APO 14 Pada COBIT 2019 - Taryoko, Taryoko; Muhammad, Alva Hendi; Kusnawi, Kusnawi (Universitas Batanghari Jambi, 2024)
The purpose of this study was to determine data management with consideration of the APO 14 domain at XYZ Agencies using the 2019 COBIT Framework. This research method uses a case study. The results of this study indicate that first, the capability level test value is entered at level 3, namely Establish. Second, the average value generated on the Capability level test value is 3.14 or 0.031, which means the XYZ agency So that it can be ensured that the XYZ agency has carried out the implementation process and is able to achieve process results in accordance with what is targeted in the APO domain 14. Third, the average GAP value produced is worth 3 with a difference of 1 value from the expected value in accordance with the 2019 COBIT provisions.